Alchemical Belief : Occultism in the Religious Culture of Early Modern England - Janacek, Bruce, 1961- (Book collections on Project MUSE., 2011)
"Explores the practice of alchemy in the context of the religious and political tensions in late Elizabethan and early Stuart England, and the use of occult knowledge to demonstrate proof of theological doctrines"--Provided by publisher.